Maternal effects on seedling development in Phaseolus vulgaris L.: the role of nitrogen management - Pereira, Vanderley José; Ribeiro-Oliveira, João Paulo [UNESP]; Silva, Andréia Cecília; Mota, Matheus Giroto Costa; Lana, Regina Maria Quintão (Taylor & Francis, 2022)
To what extent does the availability of nutrients to the mother plant affect seed quality and consequently seedling establishment? Based on this question, we evaluated the early plant establishment of the super-early BRS FC104 common bean. For that, we used seeds produced by mother plants in mutualism with nitrogen-fixing bacteria (Rhizobium leucaenae, strains SEMIA 4077, SEMIA 4080 and SEMIA 4088, at a ratio of 1:1:1) and/or fertilized with different nitrogen doses. These were applied in the physiological stages of higher nutrient demand. The cultivation system used was no-tillage. Our findings demonstrate that plants in mutualism and fertilized with 150 kg ha−1 of N-fertilizer in V 0 show increments in the seedling’s establishment ability (78, 33%). However, with this dose the percentage of vigorous normal seedlings decreases (42.0%). Mineral fertilization can be applied at any stage of the common bean development (64.27%). Mineral nitrogen causes a fixed variability in the system, regardless of the dose.
Keywords: Common bean; no-tillage systems; Rhizobium leucaenae; seed production and technology; super-early cultivar